Coping Ability Relationship With Anxiety Levels Of Chronic Kidney Failure Clients Undergoing Hemodialysis - Isnayati; Sri Atun Wahyuningsih; Elfira Awaliyah Rahmawati (Comprehensive Health Care, 2021)
Mental Health is a condition in which an individual can develop physically, mentally, spiritually, and socially so that the individual realizes his own abilities, can overcome pressures, can work productively and is able to contribute to his community (Mental Health Act 18 of 2014). One of the psychosocial problems that many people experience in daily life is anxiety. A person who has an anxiety problem can have an effect on his physical and mental. The purpose of this study is to find out the Relationship of Coping Ability With Anxiety Levels Of Chronic Kidney Failure Clients Undergoing Hemodialysis. The research method used is by Cross-Sectional approach. The research was conducted in the Hemodialysis room of RS Pelni Jakarta with a total of 30 response sampling using simple random sampling. Statistical test results show p 1.0 > 0.05 means that there is no meaningful relationship between anxiety levels and coping strategies in patients undergoing hemodialysis. conclusion and advice are that hospitals can carry out health counseling activities on anxiety management and coping strategies in patients undergoing hemodialysis.